s STUDI LITERATUR: PENGARUH APLIKASI EDIBLE COATING GEL LIDAH BUAYA (Aloe vera L.) DENGAN PENAMBAHAN CARBOXYMETHYL CELLULOSE TERHADAP MUTU BUAH APEL POTONG - Evinza Sukma Putri; Santi Diana Putri; Mentari Larashinda (Innofarm : Jurnal Inovasi Petanian, 2026)
This literature review aims to analyze the effectiveness of Edible coating from a combination of Aloe vera gel and Carboxymethyl Cellulose (CMC) in maintaining the quality of fresh-cut apples. The method used was a literature review of secondary data from Google Scholar spanning the years 2018-2023. The results indicate that the application of this composite Edible coating significantly inhibits enzymatic browning, reduces weight loss, maintains texture firmness, and suppresses microbial growth. Aloe vera gel provides natural antimicrobial and antioxidant properties, while CMC functions as a film-forming agent that improves the mechanical strength and barrier properties of the coating. The synergy between these two components creates an effective semi-permeable layer that slows down product metabolism. It is concluded that the Aloe vera gel and CMC-based Edible coating is a promising, effective, and environmentally friendly solution to extend the shelf life and maintain the quality of fresh-cut apples.